THE IMPACT OF THE T-3 SEA TOLL PROGRAM ON PRICE DISPARITY - Firmantoko; Simanjuntak , Ronald; Bashori , Achmad; Hamidi, Nazilul (Meteor STIP Marunda, 2024)
The sea toll program is to facilitate and streamline the transportation of goods through sea transportation for logistics distribution needs in archipelagic areas that do not have good transportation. The sea toll program can provide benefits not only for price stability of basic commodities but also benefits to the regional economy. The study aims to analyze the impact of sea toll benefits on price disparities. Specifically, the research was conducted in the Tarempa area of the Sea Toll Route -Route T-3. The research used quantitative method with data analysis using the Wilcoxon method. The results of data analysis show that the sea toll program for the T3 route route shows that there is a price disparity in the need for basic goods and essential materials. Data analysis from the Asymp Sig. (2-tailed) value> 0.05, namely 0.06, so H0 is accepted, where H0 there is no difference between the price before the sea toll and after the sea toll. Research conclusions based on the price of staples according to the results of the Wilcoxon test there is no difference between before the sea highway and after the sea highway.